2016
DOI: 10.1016/j.prostaglandins.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase- and cytochrome P450-derived eicosanoids in stroke

Abstract: Arachidonic acid (AA) is metabolized by cyclooxygenase (COX) and cytochrome P450 (CYP) enzymes into eicosanoids, which are involved in cardiovascular diseases and stroke. Evidence has demonstrated the important functions of these eicosanoids in regulating cerebral vascular tone, cerebral blood flow, and autoregulation of cerebral circulation. Although COX-2 inhibitors have been suggested as potential treatments for stroke, adverse events, including an increased risk of stroke, occur following long-term use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 113 publications
0
37
0
Order By: Relevance
“…For example, a lipoxin A 4 analog is neuroprotective and reduces inflammation in a rat model of cerebral ischemic reperfusion injury (Ye et al, ),15‐deoxy‐PGJ2 has antipyretic effects associated with reduction in LPS‐induced COX2 expression in the hypothalamus (Mouihate et al, ), 8,9‐ and 11,12‐EpETrE from astrocytes have angiogenic and mitogenic effects in cultured cerebral capillary endothelial cells (Zhang and Harder, ), 11,12‐EpETrE attenuates interleukin‐1β (IL‐1β)‐induced fever in the anterior hypothalamus (Nakashima et al, ), 11,12‐ and 14,15‐EpETrE have vasodilatory effects in the cerebral microcirculation (Alkayed et al, ) and astrocyte 14,15‐EpETrE enhances cell viability in oxidation‐induced ischemic injury (Terashvili et al, ; Yuan et al, ). On the other hand, abnormal levels of ARA oxylipins are also associated with brain dysfunction, such as PGE 2 , thromboxane B 2 , and leukotriene B 4 , which increase production of Aβ peptides that contributes to the formation of amyloid plaques, a hallmark of Alzheimer's disease (Amtul et al, ), 12‐HETE, a marker of brain injury (Farias et al, ), and 20‐HETE, which contributes to vasoconstriction and vasospasm in brain, which has detrimental effects in ischemic stroke (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lipoxin A 4 analog is neuroprotective and reduces inflammation in a rat model of cerebral ischemic reperfusion injury (Ye et al, ),15‐deoxy‐PGJ2 has antipyretic effects associated with reduction in LPS‐induced COX2 expression in the hypothalamus (Mouihate et al, ), 8,9‐ and 11,12‐EpETrE from astrocytes have angiogenic and mitogenic effects in cultured cerebral capillary endothelial cells (Zhang and Harder, ), 11,12‐EpETrE attenuates interleukin‐1β (IL‐1β)‐induced fever in the anterior hypothalamus (Nakashima et al, ), 11,12‐ and 14,15‐EpETrE have vasodilatory effects in the cerebral microcirculation (Alkayed et al, ) and astrocyte 14,15‐EpETrE enhances cell viability in oxidation‐induced ischemic injury (Terashvili et al, ; Yuan et al, ). On the other hand, abnormal levels of ARA oxylipins are also associated with brain dysfunction, such as PGE 2 , thromboxane B 2 , and leukotriene B 4 , which increase production of Aβ peptides that contributes to the formation of amyloid plaques, a hallmark of Alzheimer's disease (Amtul et al, ), 12‐HETE, a marker of brain injury (Farias et al, ), and 20‐HETE, which contributes to vasoconstriction and vasospasm in brain, which has detrimental effects in ischemic stroke (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the published reports on the role of 20-HETE on cerebral autoregulation in ischemic stroke is still not elucidated, and further investigation is needed. After acute ischemic injury, cerebral blood flow (CBF) is decreased at 1–2 h after reperfusion, and there is a second fall at 7 h after reperfusion (Huang et al, 2016). Administration 20-HETE synthesis inhibitors in MCAO rodents reduced infarct sizes, had no effect on the fall of CBF during the ischemic period and up to 2 h after reperfusion, but delayed or ameliorated the 2 nd fall (Dunn et al, 2008; Marumo et al, 2010; Poloyac et al, 2006; Renic et al, 2009).…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%
“…Therefore, results from these studies can only explain the role of 20-HETE on progression of outcomes of ischemic stroke. It has to be mentioned, tissue plasminogen activator (r-tPA), the only FDA-approved drug treatment for ischemic stroke patients, and COX inhibitors commonly used for acute ischemic stroke treatment, all could reduce CBF, along with other confounders such as antihypertensive drugs and vasodilators (Fan et al, 2013; Huang et al, 2016; Jordan and Powers, 2012). In fact, our recent studies using Dahl salt sensitive (SS) rats that have decreased 20-HETE production demonstrated that there is impaired autoregulation of CBF, BBB leakage, and neurodegeneration after induction of hypertension (Fan et al, 2018).…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to demonstrate the association of these polymorphisms in CYP3A4 and CYP11A1 with IS risk in Chinese population. CYP genes encode monooxygenases responsible for arachidonic acid metabolism, which is involved in cardiovascular diseases and stroke [17]. Numerous studies have suggested an association between genetic variants of CYP pathway genes and the risk of IS [18].…”
Section: Discussionmentioning
confidence: 99%